Is disulfiram innocent as it is estimated? / a review of disulfiram’s neurologic effects in the context of two cases - Altıntoprak, E.; Malkoçlu, G.; Haznedaroğlu, D. İ. and Coşkunol, H. (Journal of Dependence, 2008)
Disulfiram (DSF) is an agent that inhibits aldehyde dehydrogenase, one of the enzymes involved in alcohol metabolism. When alcohol is consumed during DSF treatment, acetaldehyde accumulates in the body, resulting in a variety of unpleasant effects. Because of this property, it has been used for approximately fifty years as an agent that promotes abstinence in the treatment of alcohol dependence. The effects of DSF interacting with alcohol are well known to clinicians, and patients are informed about this before starting treatment. However, many serious side effects that occur outside of the interaction of DSF with alcohol and are usually slow to develop can be overlooked. Neurotoxicity is one of these serious side effects. This article presents two cases of foot drop resulting from DSF use. These examples highlight the potentiation of the neurotoxic effects of DSF by the dose of DSF used and polypharmacy, and the neurotoxic effects of DSF and its metabolites are reviewed in light of the literature.